THE ROLE OF INDONESIA IN ASEAN UNDER JOKOWI’S PRO-PEOPLE DIPLOMACY - Andika, Muhammad Tri (Prosiding Seminar Nasional INDOCOMPAC)
2016 is the very important moment for ASEAN, particularly ASEAN will be economically integrated under ASEAN Economic Community framework. Certainly this would be a challenge for all ASEAN members, including Indonesia. In making AEC could produce more benefit for the members, inevitably it needs more active role from state in the region. However, it seems interesting case for Indonesia when this situation linked with the current foreign policy. Under Jokowi’s administration, he promoted “down to earth diplomacy” or also known as “pro-people diplomacy”. It seems this policy will mostly be inward-looking paradigm compared with his predecessor who emphasized strengthened role of Indonesia in the region.  Against this background, this article explores the role of Indonesia in ASEAN under a new and inward-looking president. How Indonesia should take significant presence in ASEAN under Jokowi’s “down to earth diplomacy”? What are the most likely challenges for Indonesia in dealing with ASEAN that would arise under this new situation? This article suggests that Jokowi’s administration should take careful action in defining pro-people diplomacy in order to avoid signaling a wrong message to other ASEAN members, otherwise the Jokowi’s new paradigm will easily misunderstood in the region. Keywords : Jokowi, Foreign Policy, Pro-People Diplomacy